Kinetic study on poly(3-hydroxybutyrate) production from oil palm frond juice in batch fermentation - Nurul Amalina, Alias (2014)
This research is about the kinetic study on poly(3-hydroxybutyrate), P(3HB) production from oil palm frond juice in batch fermentation. Batch fermentation experiment was conducted in 500 mL shake flasks by using Cupriavidus necator in order to produce P(3HB). Fresh oil palm frond (OPF) was pressed and undergoes certain processes such as filtration, centrifugation and sterilization to get oil palm frond juice. OPF juice were used as the fermentation substrate for P(3HB) production. In this study, the microbial growth (μ, μmax, YX/S, Ks) and product (YP/S, YP/X) kinetic parameter can be obtained by using MATLAB R2009b software. The models were fit to the data using Runge-Kutta 4th order Method by minimizing the error between experimental and predicted data using Simplex Method. Logistic Model was developed for the biomass growth model. Model for polyhydroxyalkanoates (PHA) was developed based on assumptions that each cell contains the same amount of PHA and it degrades at the same rate. Predicted data was obtained using function ode45 in MATLAB R2009b software which implements Runge-Kutta 4th Order Method. Based on the results obtained, it shows that the predicted data of biomass profile was fitted well to the experimental data but for PHB profile, the predicted data deviated quite far from the experimental data. This shown that the models developed were representing biomass growth very well. Kinetic parameters for microbial growth and production of P(3HB) were determined by using Monod equation. The values are = 0.0346h-1, Ks = 0.0930g/L, = 0.0344h-1, Yx/s= 0.4731 and = 0.0416